The effects of collaboration on logistical performance and transaction costs - José Geraldo Vidal Vieira; Hugo Tsugunobu Yoshida Yoshizak; Linda Lee Ho (International Journal of Business Science & Applied Management (IJBSAM), 2015)
This paper assesses the effect of supplier-retailer collaboration on logistical performance and transaction costs from the viewpoint of retail sector suppliers. The methodology consists of an empirical study conducted over nine months in the logistics department of a large Brazilian supermarket retailer and a survey of 125 representatives of 90 manufacturers. The results show collaboration contributes to an improvement in logistical performance related to urgent deliveries and deliveries that occur during periods of high demand. Interpersonal collaboration and joint actions contribute to the reduction of uncertainties among the participants. These joint actions, together with strategic collaboration, contribute to an increase in investment in specific assets, such as dedicated production lines or specialised vehicle fleets to serve partners. The study provides an analysis of logistical performance and transaction cost elements not previously investigated, including urgent deliveries and deliveries during periods of high demand, contract negotiation and renegotiation, waiting time for agreements to be reached, contingency logistics planning, and various cultural, psychosocial and geographical aspects of the supplier-retailer relationship. Managerial implications, research limitation and future research are also discussed.
Keywords: 650; supplier-retailer collaboration; collaboration; logistical performance; transaction costs; psychosocial relationship